KELUARGA SEBAGAI SUMBER BELAJAR BAGI PENGEMBANGAN KECERDASAN BAHASA (LINGUISTIC INTELLIGENCE) ANAK USIA TAMAN KANAK-KANAK (TK) - Rolina, Nelva (MAJALAH ILMIAH PEMBELAJARAN, 2009)
Child’s growth and development has many aspects. But, in a fact, peopleare only focus on cognitive aspect (it’s called mathematic-logicintelligence). Not only mathematic-logic intelligence, linguisticintelligence has an important role on people’s success too. We candevelop linguistic intelligence at home by family (parent). Family (parent)is one of learning resources for kindergarten children. Linguisticintelligence can be developed by good stimulation. How can do it? We cando it with creative fun activity or creative fun game. Those activity isdesigned and done by parent. Kindergarten children will be happy, andtheir linguistic intelligence will be developed.